Phosphoric acid modified kenaf fiber (K-PA) as green adsorbent for the removal of copper (II) ions towards industrial waste water effluents - Razak, Muhammad Raznisyafiq; Yusof, Nor Azah; Aris, Ahmad Zaharin; Mohmad Nasir, Hanisah; Haron, Md. Jelas; Ibrahim, Nor Azowa; Johari, Ili Syazana; Kamaruzaman, Sazlinda (Elsevier, 2020)
A novel and simple chemically modified kenaf fiber functionalized with phosphoric acid was prepared to remove copper (II) ions from waste water water samples. Combination of kenaf fiber and phosphoric acid possess renewable, green and rapid removal for waste waters treatment. In the present study, the green adsorbent was thoroughly characterized with Fourier Transform Infrared Spectroscopy (FTIR), chemical composition analysis (CHNS), Brunauer-Emmett-Teller (BET) and Scanning Electron Microscopy (SEM). Moreover, the maximum adsorption capacity towards copper (II) ions were 57.14 mg/g. The adsorption isotherm follows Langmuir model and fitted with pseudo-second-order kinetics model. The enthalpy, entropy Gibbs free energy values show the adsorption fitted with non-spontaneous and endothermic reaction. The optimal desorption process was determined during the exposure with 1 M of hydrochloric acid (95.41%) followed by sulphuric acid (82.31%) and nitric acid (81.25%). After the 2nd cycle of reusability study, the adsorption capacity slightly dropped suggesting the adsorbent only can be used for once to continue its efficiency. Hence, the K-PA was confirmed to be highly adsorptive material and having promising applications in water purification application by the encounter with real waste water matrices obtained from the electroplating (88.2% removal) and wood treatment industries (61.5% removal).